Study on single nucleotide polymorphisms of H -FABP gene in sheep - Qiao, H.Y.; Zhao, Q.J.; Yao, N.; Lu, Y.-Z.; Meng, X.-R.; Guan, Wei-Jun; Ma, Y.H.; Han Jianlin (China Science Publishing & Media Ltd., 2009)
PCR-SSCP and DNA sequencing approaches were applied to assess the single nucleotide polymorphisms (SNPs) and analyze the genetic polymorphisms at partial exon 2 and intron 2 of H-FABP(Heart fatty acid-binding protein)gene, and five sheep populations that comprised of Small-Tailed Han sheep (SH, 48), Ningxia Tan sheep (Tan, 121), Tan × SH F1 (23), Poll Dorset (48) and Suffolk (24) sheep were screened in this stuty. The result showed: (1)four SNPs at 981(G/A), 1014(A/C) 1019(T/C) and 1058 (-/G) and nine genotypes (AA, BB, CC, AB, AC, BC, AD, CD and BD) were detected using primer 2, the AA was the predominant genotype. A chi-square analysis suggested that the allele frequencies and genotype frequencies of H-FABP were in Hardy-Weinberg equilibrium except the Tan and Suffolk populations. Statistical analysis revealed a low polymorphism information content (PIC) in the Suffolk and Tan × SH F1 populations (PIC< 0.25) but an intermediate PIC in the remaining three populations (0.25< PIC <0.50). It meant that the fragment of H-FABP had polymorphisms, which could be used as a candidate gene associated gene with phenotypic traits like intramuscular fat content in different sheep populations. (2)Three genotypes (HH, Hh and hh) determined by a SNP at 2407(T-C) were detected using primer 4. The genotype frequencies were in the order of HH＞Hh＞hh. A chi-square analy-sis suggested that the allele frequencies and genotype frequencies of H-FABP were in Hardy-Weinberg equilibrium in the Tan and Poll Dorset populations, and the PIC values were low (PIC < 0.25). However, there was no polymorphisms in SH, Tan × SH F1 and Suffolk populations.